Pengaruh Citra Merek, Harga, dan Kualitas Produk Terhadap Kepuasan Konsumen Madu AG di Tulungagung - Ulfi Apriliani; Deny Yudiantoro (Jurnal Dinamika Ekonomi & Bisnis, 2023)
The purpose of this research is to examine the impact of brand image (CM), price (HG), and product quality (KP) on consumer satisfaction (KK) on Madu AG business Tulungagung Regency. The assosiative method with quantitative approach were used in this research. The sample of 60 respondents was obtained from the Madu AG consumer population in Tulungagung Regency using purposive sampling method. Data accumulation by distributing questionnaires containing statements for Madu AG’s consument. Data testing techniques using validity test, reliability test, hypothesis test, with T-test and F-test, likewise the simultaneous determination coefficient using SPSS 16.0 program. The results prove that in partially there is no significant effect between the CM variable on the Madu AG business families in Tulungagung Regency, likewise on X2 variable in partially there is no significant impact between HG on the AG Honey business families in Tulungagung Regency. However, in variable X3 partially there is a significant influence between KP and KK on Madu AG business in Tulungagung Regency. While simultaneously there is a significant influence between the variables CM, HG, KP on AG Honey business families in Tulungagung Regency with a contribution of 69.7% and the rest affected by other unspecified variables